Coping with changes in access to biodiversity and natural resources along the Mekong mainstream and tributaries - Menghoin Hok (CGIAR Research Program on Water, Land and Ecosystems, 2018)
The relationship between people and natural resources in the Mekong River Basin is intimate. Up and down the river, natural resources in the form of Non-Timber Forest Products (NTFPs), fish, water, ‘Other Aquatic Animals’ (OAAs), agro-ecosystems and other – frequently common property – resources form a significant part of livelihoods. The Lower Mekong basin falls into the territories of five countries (Myanmar, Lao PDR, Thailand, Cambodia and Vietnam), and is home to about 65 million people. The Mekong River flows almost 5,000 km and its basin covers 795,000 km2. Hydropower development is a major issue in the region as it affects biodiversity, ecosystem health, livelihoods and water governance (MRC, 2015).